Germany's New Right as Culture and Politics - Woods, R.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2007)
This is the first full-length study in English of the New Right in Germany and it breaks new ground by considering the New Right as a political and a cultural movement. The book examines the often contradictory motives that feed into New Right political pronouncements and explores the cultural thinking that feeds into extreme political commitment.
Keywords: European Union; Europe, Central—History.; Europe—Politics and government; Political theory; Political science; Cultural studies; European Union Politics; History of Germany and Central Europe; European Politics; Political Theory; Political Science; Cultural Studies